Relationship between Pulmonary TB Patient Behavior and Family Support with Treatment Adherence at Hospital in Indonesia - Nadapdap, Faskanita Maristella; Syahputra , Chairul (Jurnal Perilaku Kesehatan Terpadu, 2023)
Estimates place the number of new cases of tuberculosis (TB) at 10.4 million per year. Based on an initial survey of 10 TB patients, it was found that 6 patients were not compliant with treatment, while 4 other patients were compliant with treatment. The aim of this research was to determine the behavioral factors of pulmonary TB patients with patient treatment compliance at the RSU Pulmonary Polyclinic. Mother Thamrin Medan. The research design used in this research is an analytical survey with a cross sectional approach. The population in this study was all 58 patients and the samples were taken by a total sampling method of 58 people. Data collection methods are primary data, secondary and tertiary data. The data analysis used is the binary logistic regression test. The results showed that age had a sig-p value of 0.646> 0.05, education sig-p 0.032< 0.05, employment sig-p 1.0> 0.05, knowledge sig-p 0.012< 0.05, attitude sig-p 0.036 < 0.05, sig-p action 0.003< 0.05 and family support sig-p 0.048< 0.05.The conclusion in this study is that there is an influence of education, knowledge, attitudes, actions and family support on patient treatment compliance, while age and employment have no influence on patient treatment compliance at the RSU Pulmonary Polyclinic. Bunda Thamrin Medan. By monitoring patients, educating them to detect frequent complaints and symptoms of TB disease, and encouraging patients to report their condition to medical professionals right away, it is intended that the findings of this research can be used as informational material for research sites.